THE INFLUENCE OF STRAY KIDS AS BRAND AMBASSADOR AND BRAND IMAGE ON INTENTION TO BUY ULTRA MILK - Siti Nurin Muniro; Lu'lu Ul Maknunah (Universitas Diponegoro, 2025)
The aim of this research is to determine the influence of brand ambassador and brand image variables on the purchase intention of Ultra Milk. The method of this research is a quantitative approach with associative research. The population used is followers of Ultra Milk’s instagram account. The respondents used were 400 respondents obtained from non-probability sampling technique with purposive sampling. Multiple linear analysis was used to analyze the data in this study. The brand ambassador and brand image variables have a significance value of 0.000 < 0.05 so they partially influence intention to buy Ultra Milk. Brand ambassador and brand image also simultaneously influence the intention to buy Ultra Milk with a significance value of 0.000 < 0.05.